THE IMPACT OF CRIMINAL VERDICTS IN CIVIL PROCEEDINGS - Gjorgieva, Dijana; Doneva, Nada (International Scientific Journal Vision, 2024)
This research meticulously delves into the multifaceted effects of criminal verdicts within the context of civil proceedings, unraveling the intricate web of their consequences on both the legal framework and the broader societal fabric. Through an exhaustive and nuanced analysis encompassing normative and legal dimensions, this study endeavors to shed light on the intricate width of implications that emanate from criminal verdicts. The main goal is to make a significant contribution to the current discourse on justice, encouraging a deeper understanding of the diverse and wide spectrum of interrelations of multiple substances in the direction of achieving justice and fairness of court proceedings.